Carnaúba [Copernicia prunifera (Miller) H. E. Moore, Arecaceae], uma nova hospedeira de Raoiella indica Hirst, 1924 (Acari: Tenuipalpidae) - Sousa Neto, Eduardo P.; Souza, Izabel V.; Guzzo, Elio C.; Melo, José Wagner S. (Entomological Communications, 2021)
The red palm mite, Raoiella indica Hirst, 1924 (Tenuipalpidae), has been spreading rapidly and expanding its host range in the Neotropical region. Most of the hosts are palm trees (Arecaceae). In the present work, high population levels of R. indica are reported on “carnauba” [Copernicia prunifera (Miller) H. E. Moore, Arecaceae] in the states of Alagoas and Ceará, northeastern Brazil. This is the first report of R. indica causing damage and injuries on this palm tree native to Brazil in field. Our results allow us to conclude that carnauba is a suitable host for R. indica, with potential risk to its cultivation and exploitation.